2013
DOI: 10.1182/blood-2013-04-498964
|View full text |Cite
|
Sign up to set email alerts
|

Treatment factors affecting outcomes in HIV-associated non-Hodgkin lymphomas: a pooled analysis of 1546 patients

Abstract: Key Points Rituximab use is associated with significant improvement in all outcomes for patients with HIV-associated CD20-positive lymphomas. Infusional EPOCH chemotherapy is associated with better overall survival in patients with AIDS-related diffuse large B-cell lymphoma (DLBCL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
131
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(150 citation statements)
references
References 43 publications
14
131
1
4
Order By: Relevance
“…52,53 It is unclear, however, whether any patients with PBL were included in this analysis. Importantly, two prospective studies are evaluating the safety and efficacy of infusional EPOCH in patients with high-risk DLBCL, including PBL (NCT01092182 and CTSU-9177).…”
Section: Current Treatment Options and Emerging Therapiesmentioning
confidence: 99%
“…52,53 It is unclear, however, whether any patients with PBL were included in this analysis. Importantly, two prospective studies are evaluating the safety and efficacy of infusional EPOCH in patients with high-risk DLBCL, including PBL (NCT01092182 and CTSU-9177).…”
Section: Current Treatment Options and Emerging Therapiesmentioning
confidence: 99%
“…A detailed description of the search strategy has been previously reported 12 and is available in the Online Supplementary Appendix. We limited our dataset to only patients treated with rituximab-containing chemoimmunotherapy.…”
Section: Patients and Data Collectionmentioning
confidence: 99%
“…We created three risk groups similarly to the aaIPI: low (LR; score 0-6), intermediate (IR; score 7-10) and high risk (HR; score [11][12][13][14][15]. Distribution of these groups is described in Online Supplementary Table 3S.…”
Section: Comparison Between Arl-ipi and Aaipimentioning
confidence: 99%
“…A meta-analysis of NHL treatment in 1456 patients by Barta and colleagues concluded that rituximab is associated with a higher complete remission rate and improved progression-free survival (PFS). 19 In addition, infusional EPOCH (etoposide ϩ prednisone ϩ vincristine ϩ cyclophosphamide ϩ doxorubicin) was associated with better OS in the patients with DLBCL.…”
Section: Therapymentioning
confidence: 99%